Role of Nanofibers in Encapsulation of the Whole Cell - Sudarshan Sahu; Avinash Sharma; Soham Mukherjee; Deepak Kumar; Fatih Sen; Rupak Nagraik; Avvaru Praveen Kumar (International Journal of Polymer Science)
In the field of biomaterial research, the electrospinning device is now used to manufacture nanofibers that can be used to encapsulate whole microorganisms such as bacterial cells, funguses, viruses, and even spores. The nanofiber encapsulated cells will have greater significance in the coming future because of their wide variety of applications in various fields. Nanofibers act as microorganism reservoir systems that enhance their properties such as viability, controlled release of products, biomedical applications, and bioremediation. The effect of electrostatic forces on a droplet of liquid polymer or polymer solution is based on electrospinning. Electrospun nanofibers act as ideal native extracellular matrices for microorganisms and have also had a tremendous advantage in drug delivery systems where modern research is still underway. During electrospinning, nearly all microorganisms may be inserted into a polymer matrix that forms a composite nanofiber. The evolution in electrospinning technique over the past few decades has become promising. New ideas have been generated to enhance the techniques and improve the overall applications and properties of nanofibers. This technique has been transformed by the advent of the electrospinning machine. The electrospun nanofibers can be chemically characterized by a wide variety of procedures such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR). Electrospinning has various applications, for example, in wastewater treatment, tissue engineering, food industry, drug delivery, agriculture, and cosmetics. Nanofiber encapsulation of microorganisms increased the shelf life of the microorganisms; the cells remain viable for months. It also helps in the control release of bacterial products. The present review demonstrates the role of nanofiber in the encapsulation of the whole cell.